MHD natural convection and entropy generation in an open cavity having different horizontal porous blocks saturated with a ferrofluid - Gibanov, Nikita S.; Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Al-Salem, Khaled (Elsevier, 2018)
In this study, natural convection combined with entropy generation of Fe3O4-water nanofluid within a square open cavity filled with two different porous blocks under the influence of uniform horizontal magnetic field is numerically studied. Porous blocks of different thermal properties, permeability and porosity are located on the bottom wall. The bottom wall of the cavity is kept at hot temperature T-h, while upper open boundary is at constant cold temperature T-c and other walls of the cavity are supposed to be adiabatic. Governing equations with corresponding boundary conditions formulated in dimensionless stream function and vorticity using Brinkman-extended Darcy model for porous blocks have been solved numerically using finite difference method. Numerical analysis has been carried out for wide ranges of Hartmann number, nanoparticles volume fraction and length of the porous blocks. It has been found that an addition of spherical ferric oxide nanoparticles can order the flow structures inside the cavity. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Uniform magnetic field; Natural convection; Entropy generation; Horizonal porous blocks; Open cavity; Ferrofluid